2016
DOI: 10.1007/s00439-016-1697-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents

Abstract: Hearing loss (HL) is the most common sensory deficit in humans with causative variants in over 140 genes. With few exceptions, however, the population-specific distribution for many of the identified variants/genes is unclear. Until recently, the extensive genetic and clinical heterogeneity of deafness precluded comprehensive genetic analysis. Here, using a custom capture panel (MiamiOtoGenes), we undertook a targeted sequencing of 180 genes in a multi-ethnic cohort of 342 GJB2 mutation-negative deaf probands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 48 publications
(30 reference statements)
6
96
2
1
Order By: Relevance
“…[28][29][30][31][32][33][34] A relatively high frequency of STRC deletions was found in our Dutch population (2%), as has also been reported in other populations. 8,9 In one case (ISO31), we found causative variants in a gene that is associated with an identifiable phenotype and segregating with a recessive inheritance pattern.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34] A relatively high frequency of STRC deletions was found in our Dutch population (2%), as has also been reported in other populations. 8,9 In one case (ISO31), we found causative variants in a gene that is associated with an identifiable phenotype and segregating with a recessive inheritance pattern.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies using massively parallel sequencing have reported similar overall diagnostic rates, despite of using different technologies and testing different populations. [32][33][34]37,38 We found that causative variants in GJB2, USH2A, MYO6, STRC and MYO15A underlie HI in 14.0% of the cases in our cohort. This is in agreement with the previously published studies on the involvement of HI genes in other populations.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This represents a massive ascertainment bias, as children who are DFNB1 negative are not followed up, due to the expenses associated with genetic testing. Recently, a large, ethnically diverse, cohort study demonstrated the importance of investigating DFNB1 -negative deaf probands (Yan et al 2016). This study took a targeted panel approach in 342 probands (185 simplex and 157 multiplex families), sequenced 180 known hearing loss genes, and identified 151 variants in 119 families.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many recessive cases may be due to genetic defects in genes yet to be identified. However, recent studies using new high-throughput technologies and broader application in multi-ethnic populations report GJB2 yields of less than 25%, suggesting a larger role for other recessive genes in prelingual severe cases (Yan et al 2016; Sloan-Heggen et al 2016). …”
Section: Introductionmentioning
confidence: 99%